Fluorine-containing copolymer

By adjusting the unit composition and melt flow rate of the fluoropolymer, the prepared fluoropolymer forms a uniform thick coating on the core wire, which solves the problems of easy deformation and insufficient durability of fluoropolymer in the high-temperature environment in the prior art, and achieves efficient molding and excellent durability.

CN116917356BActive Publication Date: 2025-12-09DAIKIN INDUSTRIES LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280016581.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-26
Filing Date
2022-02-28
Publication Date
2025-12-09
Estimated Expiration
2042-02-28

AI Technical Summary

Technical Problem

Existing fluoropolymers are difficult to form a uniform and thick coating on large core wires, and are prone to deformation in high-temperature environments. They also lack sufficient wear resistance, heat aging resistance, and low hydrogen permeability, which cannot meet the needs of special applications.

Method used

A fluorinated copolymer was prepared by adjusting the content of tetrafluoroethylene, hexafluoropropylene, and perfluoropropylene ether units and the melt flow rate, thereby optimizing its moldability and durability, making it suitable for uniform coating of large core wires and stability under high temperature environments.

Benefits of technology

While achieving the formation of a uniform thick coating on the core wire, it also improved the molding speed and thickness uniformity, enhanced the wear resistance at 50℃, heat aging resistance, low hydrogen permeability, high-temperature rigidity at 100℃ and tensile creep resistance at 140℃, and improved the durability against repeated loads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004408778080000071
    Figure BDA0004408778080000071
  • Figure BDA0004408778080000191
    Figure BDA0004408778080000191
  • Figure BDA0004408778080000251
    Figure BDA0004408778080000251
Patent Text Reader

Abstract

Provided is a fluorine-containing copolymer containing tetrafluoroethylene units, hexafluoropropylene units, and perfluoro(propyl vinyl ether) units, wherein the content of the hexafluoropropylene units is 3.55 mol% to 4.10 mol% relative to the total monomer units, the content of the perfluoro(propyl vinyl ether) units is 0.39 mol% to 0.90 mol% relative to the total monomer units, and the melt flow rate at 372°C is 1.0 g / 10 minutes to 9.0 g / 10 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a fluorine-containing copolymer. BACKGROUND

[0002] Patent Document 1 describes a terpolymer containing (a) tetrafluoroethylene, (b) hexafluoropropylene at about 4 to about 12% by weight based on the weight of the terpolymer, and (c) perfluoro(ethyl vinyl ether) or perfluoro(n-propyl vinyl ether) at about 0.5 to about 3% by weight based on the weight of the terpolymer, in copolymerized form.

[0003] PRIOR ART DOCUMENTS

[0004] PATENT DOCUMENT

[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 52-109588 SUMMARY

[0006] PROBLEMS TO BE SOLVED BY THE INVENTION

[0007] An object of the present application is to provide a fluorine-containing copolymer which can form a very thick coating layer on a core wire having a very large diameter with a uniform thickness, can produce a beautiful tube, and can be formed into a film having a uniform thickness at a high molding speed, can produce a molded product which is not easily deformed even in a molten state, and which has excellent 50°C abrasion resistance, heat aging resistance, hydrogen permeation resistance, rigidity at 100°C, tensile creep resistance at 140°C, and durability to repeated load.

[0008] MEANS FOR SOLVING THE PROBLEMS

[0009] According to the present application, there is provided a fluorine-containing copolymer containing tetrafluoroethylene units, hexafluoropropylene units, and perfluoro(propyl vinyl ether) units, wherein the content of the hexafluoropropylene units is 3.55 to 4.10 mol% relative to the total monomer units, the content of the perfluoro(propyl vinyl ether) units is 0.39 to 0.90 mol% relative to the total monomer units, and the melt flow rate at 372°C is 1.0 to 9.0 g / 10 minutes.

[0010] The content of the hexafluoropropylene units relative to the total monomer units is preferably 3.55 to 3.92 mol%.

[0011] The content of the perfluoro(propyl vinyl ether) units relative to the total monomer units is preferably 0.46 to 0.85 mol%.

[0012] The melt flow rate at 372°C is preferably 2.0 to 8.0 g / 10 minutes.

[0013] The number of functional groups per 10 6 main chain carbon atoms is 90 or less.

[0014] Further, according to the present application, there is provided an injection-molded body, an extrusion-molded body, or a transfer-molded body containing the above-mentioned fluorine-containing copolymer.

[0015] Further, according to the present application, there is provided a coated electric wire provided with a coating layer containing the above-mentioned fluorine-containing copolymer.

[0016] Further, according to the present application, there is provided a molded body which is a molded body containing the above-mentioned fluorine-containing copolymer, the molded body being a pipe, a film, or a coated electric wire.

[0017] Effects of the Invention

[0018] According to the present application, it is possible to provide a fluorine-containing copolymer which can form a very thick coating layer with a uniform thickness on a core wire having a very large diameter, can produce a beautiful pipe, and can be molded into a thin film with a uniform thickness at a high molding speed, and can produce a molded body which is not easily deformed even in a molten state, and which has excellent 50°C abrasion resistance, heat aging resistance, hydrogen low permeability, 100°C high-temperature rigidity, 140°C tensile creep resistance, and durability to repeated load. DETAILED DESCRIPTION

[0019] Hereinafter, a specific embodiment of the present application will be described in detail, but the present application is not limited to the following embodiment.

[0020] The fluorine-containing copolymer of the present application contains tetrafluoroethylene (TFE) units, hexafluoropropylene (HFP) units, and perfluoro(propyl vinyl ether) (PPVE) units.

[0021] As fluorine resins, non-melt-processable fluorine resins such as polytetrafluoroethylene (PTFE) and melt-processable fluorine resins are known. PTFE has excellent properties, but has a disadvantage that melt processing is extremely difficult. On the other hand, as melt-processable fluorine resins, TFE / HFP copolymers (FEP), TFE / PPVE copolymers (PFA), and the like are known, but have a disadvantage that the heat resistance and the like are inferior to those of PTFE. Therefore, in Patent Document 1, the above-mentioned terpolymer is proposed as a fluorocarbon polymer in which these disadvantages are improved.

[0022] For a pipe for allowing a reagent to flow, it is required to have a uniform cross-sectional shape in order to allow the reagent to flow smoothly, and it is required to have abrasion resistance not to be abraded even if the reagent flows, heat aging resistance not to generate cracks even in a high-temperature environment, low gas permeability not to allow a gas such as hydrogen to permeate, high-temperature rigidity and tensile creep resistance not to be deformed even if a high-temperature reagent flows, durability to repeated load not to be deteriorated even if the pressure of the reagent frequently changes, and the like. However, the current situation is that a fluorine resin which satisfies these requirements in a good balance is not known.

[0023] It is found that by adjusting the content of the HFP units and the PPVE units of the fluorine-containing copolymer containing TFE units, HFP units and PPVE units, and the melt flow rate to a narrowly defined range, a fluorine-containing copolymer capable of being easily molded into a pipe having high moldability can be obtained, which can yield a molded article excellent in 50°C wear resistance, heat aging resistance, hydrogen low permeability, rigidity at 100°C high temperature, 140°C tensile creep resistance, and durability to repeated load.

[0024] Further, by molding the fluorine-containing copolymer of the present application by an extrusion molding method, a very thick coating layer can be formed at a uniform thickness on a core wire having a very large diameter, and a thin film having a uniform thickness can be molded at a high molding speed.

[0025] Furthermore, the fluorine-containing copolymer of the present application is less deformed by its own weight even in a molten state, and thus even in the case of being molded into a thick pipe, the obtained pipe has a beautiful cross section and a uniform thickness.

[0026] The fluorine-containing copolymer of the present application is a melt processable fluororesin. The melt processability means that the polymer can be processed by melting using conventional processing equipment such as an extruder and an injection molding machine.

[0027] The content of the HFP units of the fluorine-containing copolymer is 3.55 to 4.10 mol% with respect to the total monomer units, preferably 3.56 mol% or more, more preferably 3.57 mol% or more, further preferably 3.58 mol% or more, preferably 4.09 mol% or less, more preferably 4.05 mol% or less, further preferably 4.00 mol% or less, particularly preferably 3.95 mol% or less, most preferably 3.92 mol% or less. When the content of the HFP units is too small, a molded article excellent in 50°C wear resistance and heat aging resistance cannot be obtained. When the content of the HFP units is too large, a molded article excellent in hydrogen low permeability, rigidity at 100°C high temperature, 140°C tensile creep resistance, and durability to repeated load cannot be obtained.

[0028] The content of the PPVE units of the fluorine-containing copolymer is 0.39 to 0.90 mol% with respect to the total monomer units, preferably 0.43 mol% or more, more preferably 0.46 mol% or more, further preferably 0.52 mol% or more, particularly preferably 0.55 mol% or more, most preferably 0.58 mol% or more, more preferably 0.87 mol% or less, further preferably 0.85 mol% or less, particularly preferably 0.80 mol% or less, most preferably 0.77 mol% or less. When the content of the PPVE units is too small, a molded article excellent in 50°C wear resistance and heat aging resistance cannot be obtained. When the content of the PPVE units is too large, a molded article excellent in hydrogen low permeability and rigidity at 100°C high temperature cannot be obtained.

[0029] The content of the TFE units of the fluorine-containing copolymer is preferably 95.00 to 96.06 mol%, more preferably 95.08 mol% or more, further preferably 95.15 mol% or more, more further preferably 95.25 mol% or more, particularly preferably 95.31 mol% or more, more preferably 96.01 mol% or less, further preferably 95.97 mol% or less, more further preferably 95.90 mol% or less, particularly preferably 99.45 mol% or less, most preferably 99.42 mol% or less, with respect to the total monomer units. In addition, the content of the TFE units can be selected so that the total content of the HFP units, the PPVE units, the TFE units, and the other monomer units is 100 mol%.

[0030] The fluorine-containing copolymer of the present application can be a copolymer containing only the above three monomer units, or a copolymer containing the above three monomer units and other monomer units, as long as it contains the above three monomer units.

[0031] As the other monomer, there is no particular limitation as long as it is a monomer copolymerizable with TFE, HFP, and PPVE, and it can be a fluorine-containing monomer or a non-fluorine-containing monomer.

[0032] As the fluorine-containing monomer, at least one selected from the group consisting of trifluorochloroethylene, fluoroethylene, vinylidene fluoride, trifluoroethylene, hexafluoroisobutene, CH2=CZ 1 (CF2) n Z 2 (in the formula, Z 1 is H or F, Z 2 is H, F, or Cl, and n is an integer of 1 to 10), perfluoro(alkyl vinyl ether) [PAVE] represented by CF2=CF-ORf 1 (in the formula, Rf 1 is a perfluoroalkyl group having 1 to 8 carbon atoms), alkyl perfluoro vinyl ether derivative represented by CF2=CF-O-CH2-Rf 2 (in the formula, Rf 2 is a perfluoroalkyl group having 1 to 5 carbon atoms), perfluoro-2,2-dimethyl-1,3-dioxolene [PDD], and perfluoro-2-methylene-4-methyl-1,3-dioxolane [PMD] can be mentioned.

[0033] As the monomer represented by CH2=CZ 1 (CF2) n Z 2 , CH2=CH-C4F9, CH2=CH-C6F 13 , CH2=CF-C3F6H, and the like can be mentioned.

[0034] As CF2 = CF - ORf 1 Examples of perfluorinated (alkyl vinyl ethers) include CF2=CF-OCF3 and CF2=CF-OCF2CF3.

[0035] Examples of non-fluorinated monomers include hydrocarbon monomers capable of copolymerizing with TFE, HFP, and PPVE. Examples of hydrocarbon monomers include: olefins such as ethylene, propylene, butene, and isobutylene; alkyl vinyl ethers such as ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, isobutyl vinyl ether, and cyclohexyl vinyl ether; vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl valerate, vinyl pentanoate, vinyl hexanoate, vinyl octanoate, vinyl decanoate, vinyl tert-carbonate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl benzoate, p-tert-butylbenzoate, vinyl cyclohexanecarboxylate, and vinyl monochloroacetate. Vinyl esters such as vinyl adipate, vinyl acrylate, vinyl methacrylate, vinyl crotonate, vinyl sorbate, vinyl cinnamate, vinyl undecenoate, vinyl glycolate, vinyl hydroxypropionate, vinyl hydroxybutyrate, vinyl hydroxyvalerate, vinyl hydroxyisobutyrate, and vinyl hydroxycyclohexanecarboxylate; alkyl allyl ethers such as ethyl allyl ether, propyl allyl ether, butyl allyl ether, isobutyl allyl ether, and cyclohexyl allyl ether; and alkyl allyl esters such as ethyl allyl ester, propyl allyl ester, butyl allyl ester, isobutyl allyl ester, and cyclohexyl allyl ester.

[0036] As non-fluorinated monomers, they can also be hydrocarbon monomers containing functional groups capable of copolymerizing with TFE, HFP, and PPVE. Examples of hydrocarbon monomers containing functional groups include hydroxyalkyl vinyl ethers such as hydroxyethyl vinyl ether, hydroxypropyl vinyl ether, hydroxybutyl vinyl ether, hydroxyisobutyl vinyl ether, and hydroxycyclohexyl vinyl ether; non-fluorinated monomers with glycidyl groups such as glycidyl vinyl ether and glycidyl allyl ether; non-fluorinated monomers with amino groups such as aminoalkyl vinyl ether and aminoalkyl allyl ether; non-fluorinated monomers with amide groups such as (meth)acrylamide and hydroxymethylacrylamide; bromine-containing alkenes, iodine-containing alkenes, bromine-containing vinyl ethers, and iodine-containing vinyl ethers; and non-fluorinated monomers with nitrile groups.

[0037] The content of other monomer units in the fluorinated copolymer of the present invention is preferably 0 mol% to 1.06 mol% relative to all monomer units, more preferably 1 mol% or less, further preferably 0.5 mol% or less, and particularly preferably 0.1 mol% or less.

[0038] The melt flow rate (MFR) of the fluorine-containing copolymer is preferably 1.0 to 9.0 g / 10 minutes, more preferably 1.2 g / 10 minutes or more, further preferably 1.5 g / 10 minutes or more, still further preferably 2.0 g / 10 minutes or more, yet further preferably 3.0 g / 10 minutes or more, especially further preferably 4.0 g / 10 minutes or more, particularly preferably 4.5 g / 10 minutes or more, most preferably 5.0 g / 10 minutes or more, and preferably 8.9 g / 10 minutes or less, more preferably 8.5 g / 10 minutes or less, further preferably 8.0 g / 10 minutes or less, still further preferably 7.0 g / 10 minutes or less, yet further preferably 6.0 g / 10 minutes or less, particularly preferably 5.5 g / 10 minutes or less, most preferably 5.0 g / 10 minutes or less. By setting the MFR of the fluorine-containing copolymer within the above range, the moldability of the copolymer is improved, and a molded article excellent in 50°C wear resistance, heat aging resistance, hydrogen permeability, rigidity at 100°C, tensile creep resistance at 140°C, and durability to repeated load can be obtained. In addition, by setting the MFR of the fluorine-containing copolymer within the above range, the fluorine-containing copolymer is less likely to be deformed by its own weight in a molten state.

[0039] In the present application, the melt flow rate is a value obtained by using a melt flow indexer G-01 (manufactured by Toyo Seiki Kenki K.K.) as the mass (g / 10 minutes) of polymer flowing per 10 minutes from a die having an inner diameter of 2 mm and a length of 8 mm under a load of 5 kg at 372°C in accordance with ASTM D-1238.

[0040] The MFR can be adjusted by adjusting the kind and amount of polymerization initiator used when polymerizing the monomers, the kind and amount of chain transfer agent, and the like.

[0041] The fluorine-containing copolymer of the present application can have a functional group or can not have a functional group. The functional group is a functional group present at the end of the main chain or the end of the side chain of the fluorine-containing copolymer, and a functional group present in the main chain or the side chain. Typical functional groups are -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, and -CH2OH.

[0042] The number of functional groups per 10 6 main chain carbon atoms of the fluorine-containing copolymer is preferably 90 or less, more preferably 70 or less, further preferably 50 or less, still further preferably 40 or less, yet further preferably 30 or less, particularly preferably 20 or less, most preferably less than 15. By setting the number of functional groups of the fluorine-containing copolymer within the above range, a molded article in which fluorine ions are less likely to be eluted into a reagent such as hydrogen peroxide water can be obtained.

[0043] The number of functional groups of the fluorine-containing copolymer is the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, and -CH2OH.

[0044] The number of -CF2H per 10 6 main chain carbon atoms of the fluorine-containing copolymer is preferably 50 or less, more preferably 40 or less, further preferably 30 or less, still further preferably 20 or less, particularly preferably less than 15, and most preferably 10 or less.

[0045] The total number of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, and -CONH2 per 10 6 main chain carbon atoms of the fluorine-containing copolymer is preferably 80 or less, more preferably 70 or less, further preferably 50 or less, still further preferably 40 or less, particularly more preferably 30 or less, particularly preferably 20 or less, and most preferably less than 15.

[0046] The identification of the kind of the above functional group and the measurement of the number of functional groups can be performed using infrared spectroscopy.

[0047] As for the number of functional groups, specifically, the measurement is performed using the following method. First, the above fluorine-containing copolymer is cold-pressed to produce a film having a thickness of 0.25 to 0.30 mm. The film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the above fluorine-containing copolymer and a differential spectrum from a background spectrum of a completely fluorinated sample having no functional group. The number of functional groups N per 1 x 10 6 carbon atoms in the above fluorine-containing copolymer is calculated from the absorption peak of a specific functional group appearing in the differential spectrum according to the following formula (A).

[0048] N = I x K / t (A)

[0049] I: absorbance

[0050] K: correction factor

[0051] t: thickness of the film (mm)

[0052] For reference, as for some functional groups, the absorption frequency, molar absorption coefficient, and correction factor are shown in Table 1. In addition, the molar absorption coefficient is determined from the FT-IR measurement data of a low molecular model compound.

[0053] [Table 1]

[0054] Table 1

[0055]

[0056] -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, -CH2CONH2, respectively, are lower than the absorption frequencies of -CF2H, -COF, free -COOH and bonded -COOH, -COOCH3, -CONH2, respectively, as shown in the table. 1 ).

[0057] For example, the number of functional groups of -COF is the total number of the number of functional groups calculated from the absorption peak at 1883 cm"1due to -CF2COF and the number of functional groups calculated from the absorption peak at 1840 cm"1due to -CH2COF. 1 The number of functional groups of -COOH is the total number of the number of functional groups calculated from the absorption peak at 1710 cm"1due to -CF2COOH and the number of functional groups calculated from the absorption peak at 1690 cm"1due to -CH2COOH. 1 The number of functional groups of -COOH is the total number of the number of functional groups calculated from the absorption peak at 1710 cm"1due to -CF2COOH and the number of functional groups calculated from the absorption peak at 1690 cm"1due to -CH2COOH.

[0058] In addition, the number of -CF2H groups can also be measured by F-NMR measurement, with the measurement temperature set to (melting point of the polymer + 20) °C. 19 The number of -CF2H groups is calculated from the peak integral value of the -CF2H group.

[0059] The functional group is a functional group present at the end of the main chain or the end of the side chain of the fluorine-containing copolymer and a functional group present in the main chain or the side chain. The number of functional groups can be the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, and -CH2OH.

[0060] The above functional group is introduced into the fluorine-containing copolymer, for example, by a chain transfer agent or a polymerization initiator used when the fluorine-containing copolymer is produced. For example, in the case where an alcohol is used as a chain transfer agent or a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced to the end of the main chain of the fluorine-containing copolymer. In addition, by polymerizing a monomer having a functional group, the above functional group is introduced to the end of the side chain of the fluorine-containing copolymer.

[0061] By subjecting the fluorine-containing copolymer having such a functional group to a wet heat treatment, a fluorination treatment, or the like, a fluorine-containing copolymer having a number of functional groups within the above range can be obtained. The fluorine-containing copolymer of the present application is preferably subjected to a wet heat treatment or a fluorination treatment, and more preferably to a fluorination treatment. The fluorine-containing copolymer of the present application also preferably has a -CF3 terminal group.

[0062] The melting point of the fluorine-containing copolymer is preferably 260 to 290°C, and more preferably 273 to 290°C. By having a melting point within the above range, the moldability of the copolymer is further improved, and a molded body which is less likely to deform even in a molten state, and which is more excellent in 50°C wear resistance, heat aging resistance, low hydrogen permeability, rigidity at 100°C, tensile creep resistance at 140°C, and durability to repeated load can be obtained.

[0063] In the present application, the melting point can be measured using a differential scanning calorimeter [DSC].

[0064] The hydrogen permeation coefficient of the fluorine-containing copolymer is preferably 1900 cm 3 • mm / (m 2 • 24 h • atm) or less. The fluorine-containing copolymer of the present application has excellent hydrogen low permeability due to appropriate adjustment of the contents of HFP units and PPVE units, and the melt flow rate.

[0065] In the present application, the hydrogen permeation coefficient can be measured under conditions of a test temperature of 60°C and a test humidity of 0% RH. The hydrogen permeation coefficient can be measured by the method described in the examples.

[0066] The amount of dissolved fluorine ions detected in the immersion test in hydrogen peroxide water of the fluorine-containing copolymer of the present application is preferably 4.0 ppm or less, more preferably 3.0 ppm or less, and further preferably 2.8 ppm or less on a mass basis.

[0067] In the present application, the immersion test in hydrogen peroxide water can be performed as follows: using the fluorine-containing copolymer, a test piece having a weight corresponding to 10 pieces of a molded body (15 mm x 15 mm x 0.2 mm) is prepared, and a polypropylene-made bottle in which the test piece and 15 g of a 3 mass% hydrogen peroxide aqueous solution are placed is placed in a constant-temperature bath at 95°C and left for 20 hours.

[0068] The fluorine-containing copolymer of the present application can be produced by any one of bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, and the like. In these polymerization methods, each condition such as temperature, pressure, a polymerization initiator, a chain transfer agent, a solvent, and other additives can be appropriately set according to the composition and amount of the fluorine-containing copolymer desired.

[0069] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical initiator can be used.

[0070] As the oil-soluble radical polymerization initiator, a publicly known oil-soluble peroxide can be used, and the following substances can be exemplified as representative examples:

[0071] dialkyl peroxycarbonates such as di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, and the like;

[0072] tert-butyl peroxyisobutyrate, tert-butyl peroxyneopentanoate, and the like;

[0073] dialkyl peroxides such as di-tert-butyl peroxide, and the like;

[0074] di[fluoro (or fluoro-chloro) acyl] peroxides, and the like.

[0075] As the di[fluoro (or fluoro-chloro) acyl] peroxide, diacyl peroxide represented by [(RfCOO)-]2 (Rf is perfluoroalkyl, ω-hydroperfluoroalkyl or fluoro-chloroalkyl) can be given.

[0076] As the di[fluoro (or fluoro-chloro) acyl] peroxide, diacyl peroxide represented by [(RfCOO)-]2 (Rf is perfluoroalkyl, ω-hydroperfluoroalkyl or fluoro-chloroalkyl) can be given.

[0077] As the water-soluble radical polymerization initiator, a publicly known water-soluble peroxide can be used, and for example, ammonium, potassium, sodium salts of peroxysulfuric acid, peroxylboric acid, perchloric acid, peroxylphosphoric acid, peroxylcarbonic acid and the like, t-butyl peroxy maleate, t-butyl hydroperoxide and the like can be given. A reducing agent such as a sulfurous acid salt can also be contained, and the amount thereof can be 0.1 to 20 times the amount of the peroxide.

[0078] As the chain transfer agent, for example, hydrocarbons such as ethane, isopentane, n-hexane, cyclohexane and the like; aromatic compounds such as toluene, xylene and the like; ketones such as acetone and the like; acetic acid esters such as ethyl acetate, butyl acetate and the like; alcohols such as methanol, ethanol, 2,2,2-trifluoroethanol and the like; mercaptans such as methyl mercaptan and the like; halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, chloromethane and the like; 3-fluorobenzotrifluoride and the like can be given. The amount of addition can be varied depending on the magnitude of the chain transfer constant of the compound used, and generally, 0.01 to 20 parts by mass is used per 100 parts by mass of the solvent.

[0079] For example, in the case where a dialkyl carbonate peroxide, a di[fluoro (or fluoro-chloro) acyl] peroxide or the like is used as a polymerization initiator, the molecular weight of the obtained fluorine-containing copolymer becomes excessively high, and it is sometimes difficult to adjust to a desired melt flow rate, but the molecular weight can be adjusted using a chain transfer agent. It is particularly preferable to produce the fluorine-containing copolymer by suspension polymerization using a chain transfer agent such as an alcohol and an oil-soluble radical polymerization initiator.

[0080] As the solvent, water, a mixed solvent of water and an alcohol, or the like can be given. In addition, a monomer used in the polymerization of the fluorine-containing copolymer of the present application can also be used as the solvent.

[0081] In the suspension polymerization, a fluorine-based solvent can also be used in addition to water. As the fluorine-based solvent, a hydrochlorofluoroalkane such as CH3CCIF2, CH3CC12F, CF3CF2CC12H, CF2C1CF2CFHC1, and the like; a chlorofluoroalkane such as CF2C1CFCF2CF3, CF3CFCF1CF3, and the like; a perfluoroalkane such as perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, CF3CF2CF2CF2CF2CF3, and the like; and the like can be given, of which a perfluoroalkane is preferable. The amount of the fluorine-based solvent is preferably 10 to 100 parts by mass relative to 100 parts by mass of the solvent from the aspects of the suspension property and economy.

[0082] The polymerization temperature is not particularly limited, and can be 0 to 100°C. In addition, in the case where a dialkyl carbonate peroxide, a di[fluoro (or fluoro-chloro) acyl] peroxide or the like is used as a polymerization initiator, or in the case where the decomposition speed of the polymerization initiator is excessively fast, it is preferable to adopt a lower polymerization temperature in which the polymerization temperature is in the range of 0 to 35°C.

[0083] The polymerization pressure is appropriately determined depending on the kind of the solvent used, the amount of the solvent, the vapor pressure, other polymerization conditions such as the polymerization temperature, and the like, and can be usually 0 to 9.8 MPaG. The polymerization pressure is preferably 0.1 MPaG to 5 MPaG, more preferably 0.5 MPaG to 2 MPaG, and further preferably 0.5 MPaG to 1.5 MPaG. In addition, when the polymerization pressure is 1.5 MPaG or more, the production efficiency can be improved.

[0084] As an additive in the polymerization, a suspension stabilizer, for example, can be mentioned. As the suspension stabilizer, there is no particular limitation as long as it is a publicly known suspension stabilizer, and methylcellulose, polyvinyl alcohol, or the like can be used. If a suspension stabilizer is used, the suspension particles generated by the polymerization reaction are stably dispersed in the aqueous medium, and therefore, even if a reaction tank made of SUS, which has not been subjected to an anti-adhesion treatment such as glass lining, is used, the suspension particles are not easily adhered to the reaction tank. Therefore, a reaction tank that can withstand high pressure can be used, and thus the polymerization under high pressure can be performed, and the production efficiency can be improved. In contrast, in the case where the polymerization is performed without using a suspension stabilizer, if a reaction tank made of SUS, which has not been subjected to an anti-adhesion treatment, is used, the suspension particles can be adhered to reduce the production efficiency. The concentration of the suspension stabilizer with respect to the aqueous medium can be appropriately adjusted depending on the conditions.

[0085] In the case where the aqueous dispersion liquid containing the fluorine-containing polymer is obtained by the polymerization reaction, the dried fluorine-containing polymer can be recovered by allowing the fluorine-containing copolymer contained in the aqueous dispersion liquid to be coagulated, washed, and dried. In the case where the fluorine-containing copolymer is obtained in the form of a slurry by the polymerization reaction, the dried fluorine-containing polymer can be recovered by taking out the slurry from the reaction vessel and washing and drying. By drying, the fluorine-containing copolymer can be recovered in the form of a powder.

[0086] The fluorine-containing copolymer obtained by the polymerization can be molded into pellets. As the molding method into pellets, there is no particular limitation, and publicly known methods can be used. For example, a method in which the fluorine-containing copolymer is melt-extruded using a single-screw extruder, a twin-screw extruder, a tandem extruder, and the like, and cut into a predetermined length to be molded into a pellet shape, and the like can be mentioned. The extrusion temperature at the time of melt-extrusion needs to be changed depending on the melt viscosity of the fluorine-containing copolymer, the production method, and the like, and is preferably the melting point of the fluorine-containing copolymer + 20°C to the melting point of the fluorine-containing copolymer + 140°C. The cutting method of the fluorine-containing copolymer is not particularly limited, and publicly known methods such as a wire-cutting method, a hot-cutting method, an underwater-cutting method, a sheet-cutting method, and the like can be adopted. The obtained pellets can also be heated to remove volatile components in the pellets (degassing treatment). The obtained pellets can also be treated by being brought into contact with warm water at 30°C to 200°C, water vapor at 100°C to 200°C, or hot air at 40°C to 200°C.

[0087] The fluorine-containing copolymer obtained by polymerization can also be heated to a temperature of 100°C or higher in the presence of air and water (wet heat treatment). As a method of the wet heat treatment, for example, a method in which the fluorine-containing copolymer obtained by polymerization is melted and extruded while supplying air and water using an extruder can be mentioned. By the wet heat treatment, the thermally unstable functional groups of the fluorine-containing copolymer, -COF, -COOH, etc., can be converted to the relatively thermally stable -CF2H, and the total number of -COF and -COOH of the fluorine-containing copolymer, and the total number of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, and -CONH2 can be easily adjusted to the above range. In addition to air and water, by heating the fluorine-containing copolymer in the presence of an alkali metal salt, the conversion reaction to -CF2H can be promoted. However, it should be noted that, depending on the use of the fluorine-containing copolymer, contamination by the alkali metal salt should be avoided.

[0088] The fluorine-containing copolymer obtained by polymerization can also be subjected to fluorination treatment. The fluorination treatment can be performed by bringing the fluorine-containing copolymer not subjected to the fluorination treatment into contact with a fluorine-containing compound. By the fluorination treatment, the thermally unstable functional groups of the fluorine-containing copolymer, -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2, etc., and the relatively thermally stable functional groups, -CF2H, etc., can be converted to the extremely thermally stable -CF3. As a result, the total number of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2, and -CF2H of the fluorine-containing copolymer can be easily adjusted to the above range.

[0089] As the fluorine-containing compound, there is no particular limitation, and a fluorine radical source that generates a fluorine radical under the fluorination treatment conditions can be mentioned. As the above fluorine radical source, F2gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, fluorinated halogen (e.g., IF5, CIF3), etc. can be mentioned.

[0090] The fluorine radical source such as F2gas can be used at a concentration of 100%, but from the viewpoint of safety, it is preferable to be mixed with and diluted to 5 to 50 mass% with respect to a non-reactive gas, and more preferably to 15 to 30 mass%. As the above non-reactive gas, nitrogen, helium, argon, etc. can be mentioned, and from the viewpoint of economy, nitrogen is preferable.

[0091] The conditions of the fluorination treatment are not particularly limited, and the fluorinated copolymer in a molten state can be brought into contact with a fluorinated compound, but generally, the treatment can be performed at a temperature lower than the melting point of the fluorinated copolymer, preferably at a temperature of 20°C to 220°C, more preferably at a temperature of 100°C to 200°C. The above fluorination treatment is generally performed for 1 hour to 30 hours, preferably for 5 hours to 25 hours. The fluorination treatment is preferably a treatment in which the non-fluorinated copolymer is brought into contact with fluorine gas (F2 gas).

[0092] The fluorinated copolymer of the present application can also be mixed with other components as needed to obtain a composition. As the other components, fillers, plasticizers, processing aids, release agents, pigments, flame retardants, lubricants, light stabilizers, weathering stabilizers, electrically conductive agents, antistatic agents, ultraviolet absorbers, antioxidants, blowing agents, perfumes, oils, softening agents, dehydrofluorination agents, and the like can be given.

[0093] As the fillers, for example, silica, kaolin, clay, organically modified clay, talc, mica, alumina, calcium carbonate, calcium terephthalate, titanium oxide, calcium phosphate, calcium fluoride, lithium fluoride, crosslinked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, glass fibers, and the like can be given. As the electrically conductive agents, carbon black and the like can be given. As the plasticizers, dioctyl phthalate, pentaerythritol, and the like can be given. As the processing aids, carnauba wax, sulfone compounds, low-molecular-weight polyethylene, fluorine-based processing aids, and the like can be given. As the dehydrofluorination agents, organo-oniums, amidines, and the like can be given.

[0094] In addition, as the above other components, other polymers other than the above fluorinated copolymer can also be used. As the other polymers, fluororesins other than the above fluorinated copolymer, fluororubbers, non-fluorinated polymers, and the like can be given.

[0095] As the method for producing the above composition, a method in which the fluorinated copolymer and the other components are mixed in a dry manner, a method in which the fluorinated copolymer and the other components are preliminarily mixed with a mixer, followed by melt-kneading with a kneader, a melt extruder, or the like, and the like can be given.

[0096] The fluorinated copolymer of the present application or the above composition can be used as a processing aid, a molding material, or the like, and is preferably used as a molding material. In addition, an aqueous dispersion, a solution, a suspension, and a copolymer / solvent system of the fluorinated copolymer of the present application can also be used as a coating material, and can be applied as a coating, or used for encapsulation, impregnation, film casting. However, the fluorinated copolymer of the present application is preferably used as the above molding material because of the above characteristics.

[0097] The fluorinated copolymer of the present application or the above composition can also be molded to obtain a molded body.

[0098] The method of molding the above-mentioned fluorine-containing copolymer or the above-mentioned composition is not particularly limited, and injection molding, extrusion molding, compression molding, blow molding, transfer molding, rotational molding, slip-in molding, and the like can be given. Among them, extrusion molding, compression molding, injection molding, or transfer molding is preferred, and injection molding, extrusion molding, or transfer molding is more preferred because a molded body can be produced at a high productivity, and injection molding or extrusion molding is further preferred. That is, as the molded body, extrusion molded body, compression molded body, injection molded body, or transfer molded body is preferred because it can be produced at a high productivity, and injection molded body, extrusion molded body, or transfer molded body is more preferred, and injection molded body or extrusion molded body is further preferred.

[0099] As the molded body containing the fluorine-containing copolymer of the present application, for example, nut, bolt, joint, film, bottle, gasket, wire covering, tube, hose, pipe, valve, sheet, seal, gasket, tank, roller, container, tap, connector, filter housing, filter cover, flow meter, pump, wafer carrier, wafer cassette, and the like can be given.

[0100] The fluorine-containing copolymer of the present application, the above-mentioned composition, or the above-mentioned molded body can be used, for example, for the following uses.

[0101] Film for food packaging, lining material for fluid delivery line used in food manufacturing process, gasket, sealing material, sheet, and the like fluid delivery member for food manufacturing device;

[0102] Chemical stopper, packaging film, lining material for fluid delivery line used in chemical manufacturing process, gasket, sealing material, sheet, and the like reagent delivery member;

[0103] Lining member for inner surface of reagent tank and piping of chemical plant and semiconductor factory;

[0104] O-ring / tube / gasket, valve core material, hose, sealing material, and the like fuel delivery member used in fuel system and peripheral device of automobile, hose, sealing material, and the like used in AT device of automobile;

[0105] Flange gasket of carburetor, shaft seal, valve stem seal, sealing material, hose, and the like hose for brake device, air conditioning hose, radiator hose, wire covering material, and the like other automobile member used in engine and peripheral device of automobile;

[0106] O-ring, tube, gasket, valve core material, hose, sealing material, roller, gasket, diaphragm, joint, and the like reagent delivery member for semiconductor device;

[0107] Coating roller, hose, tube, ink container, and the like coating and ink member used in coating device;

[0108] pipes, hoses, belts, gaskets, joints and the like for food and drink delivery members, food packaging materials, glass cooking equipment;

[0109] pipes, hoses and the like for waste liquid delivery members;

[0110] pipes, hoses and the like for high-temperature liquid delivery members;

[0111] pipes, hoses and the like for steam piping members;

[0112] anticorrosion belts and the like for piping wound around decks and the like of ships;

[0113] various coating materials such as wire coating materials, optical fiber coating materials, transparent surface coating materials provided on the light incident side surface of a photovoltaic element of a solar cell, and back surface agents;

[0114] diaphragms of diaphragm pumps, various gaskets and the like, and sliding members;

[0115] agricultural films, weather-resistant covers for various roof materials and side walls, and the like;

[0116] coating materials for interior materials used in the building field, glass-based coating materials such as non-combustible fire safety glass, and the like;

[0117] lining materials such as laminated steel sheets used in the field of home electronics and the like.

[0118] As the fuel delivery members used in the fuel systems of the above-described automobiles, fuel hoses, packing hoses, evaporator hoses and the like can be further mentioned. The above-described fuel delivery members can also be used as fuel delivery members for use in acid-resistant gasoline, alcohol-resistant fuel, and fuel added with gasoline additives such as methyl tert-butyl ether-resistant and amine-resistant gasoline.

[0119] The above-described chemical medicine stoppers and packaging films have excellent chemical resistance against acids and the like. In addition, as the above-described reagent delivery members, anticorrosion belts wound around chemical equipment piping can be mentioned.

[0120] As the above-described shaped bodies, radiator water chambers of automobiles, reagent tanks, bellows, bulkheads, rollers, gasoline tanks, waste liquid delivery containers, high-temperature liquid delivery containers, fishing and fish farming tanks and the like can be further mentioned.

[0121] As the above-described shaped bodies, further members used in bumpers, door trims, instrument panels of automobiles, food processing devices, cooking machines, water- and oil-repellent glass, lighting-related instruments, indicator panels and housings of OA instruments, electrically illuminated signs, display screens, liquid crystal display screens, mobile telephones, printer chassis, electrical and electronic parts, groceries, garbage cans, bathtubs, integral bathrooms, ventilation fans, lighting frames and the like can be mentioned.

[0122] The molded body containing the fluorine-containing copolymer of the present application is excellent in 50°C wear resistance, heat aging resistance, hydrogen low permeability, rigidity at 100°C high temperature, 140°C tensile creep resistance, and durability against repeated load, and thus can be suitably used for nuts, bolts, joints, gaskets, valves, cocks, connectors, filter housings, filter covers, flowmeters, pumps, and the like. Among them, it can be suitably used as a pipe member (particularly, a valve or a joint) used in the transport of a reagent, and a flowmeter main body having a flow path of a reagent in a flowmeter. The pipe member and the flowmeter main body of the present application are excellent in 50°C wear resistance, heat aging resistance, hydrogen low permeability, rigidity at 100°C high temperature, 140°C tensile creep resistance, and durability against repeated load. Thus, the pipe member and the flowmeter main body of the present application are not easily damaged even if they are repeatedly subjected to stress according to the start and stop of the flow of a reagent, and the change of flow rate.

[0123] The molded body containing the fluorine-containing copolymer of the present application is excellent in 50°C wear resistance, heat aging resistance, hydrogen low permeability, rigidity at 100°C high temperature, 140°C tensile creep resistance, and durability against repeated load, and thus can be suitably used as a gasket, a gasket, and the like. The compressed member of the present application can be a gasket or a gasket. The gasket or the gasket of the present application can be manufactured at low cost by injection molding, and is excellent in 50°C wear resistance, heat aging resistance, hydrogen low permeability, rigidity at 100°C high temperature, 140°C tensile creep resistance, and durability against repeated load.

[0124] The size and shape of the compressed member of the present application can be appropriately set according to the use, and are not particularly limited. The shape of the compressed member of the present application can be, for example, ring-shaped. In addition, the compressed member of the present application can have a circular, elliptical, or quadrangular shape with rounded corners in plan view, and can have a through hole in the center portion thereof.

[0125] The compressed member of the present application is preferably used as a member for constituting a non-aqueous electrolyte battery. The compressed member of the present application is excellent in 50°C wear resistance, heat aging resistance, hydrogen low permeability, rigidity at 100°C high temperature, 140°C tensile creep resistance, and durability against repeated load, and is particularly suitable as a member used in a state in which it is in contact with a non-aqueous electrolyte in a non-aqueous electrolyte battery. That is, the compressed member of the present application can have a liquid contact surface with a non-aqueous electrolyte in a non-aqueous electrolyte battery.

[0126] As a non-aqueous electrolyte battery, there is no particular limitation as long as it is a battery having a non-aqueous electrolyte, and examples thereof include a lithium ion secondary battery, a lithium ion capacitor, and the like. In addition, as a member constituting a non-aqueous electrolyte battery, examples thereof include a sealing member, an insulating member, and the like.

[0127] The non-aqueous electrolyte solution is not particularly limited, and one or two or more kinds of known solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate can be used. The non-aqueous electrolyte battery can further have an electrolyte. The electrolyte is not particularly limited, and LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, or the like can be used.

[0128] The compressed member of the present application can be preferably used, for example, as a sealing member such as a sealing gasket, a sealing washer, and the like, an insulating member such as an insulating gasket, an insulating washer, and the like. The sealing member is a member used for preventing leakage of a liquid or a gas or intrusion of a liquid or a gas from the outside. The insulating member is a member used for electrical insulation. The compressed member of the present application can also be a member used for both sealing and insulation.

[0129] The compressed member of the present application is excellent in 50°C abrasion resistance, heat aging resistance, hydrogen low permeability, rigidity at 100°C, 140°C tensile creep resistance, durability to repeated load, and thus can be suitably used as a sealing member for a non-aqueous electrolyte battery or an insulating member for a non-aqueous electrolyte battery. In addition, the compressed member of the present application has excellent insulating properties because it contains the fluorine-containing copolymer described above. Thus, in the case where the compressed member of the present application is used as an insulating member, it is firmly bonded to two or more conductive members, and short circuit is prevented for a long period of time.

[0130] The fluorine-containing copolymer of the present application can form a very thick coating layer in a uniform thickness on a core wire having a very large diameter by an extrusion molding method, and thus can be suitably used as a material for forming a wire coating. The coated wire having a coating layer containing the fluorine-containing copolymer of the present application has almost no variation in outer diameter, and thus has excellent electrical properties.

[0131] The coated wire has a core wire and a coating layer containing the fluorine-containing copolymer of the present application provided around the core wire. For example, an extrusion molded body obtained by melt-extrusion molding the fluorine-containing copolymer of the present application on a core wire can be used as the coating layer. The coated wire is suitably used for LAN cable (Ethernet Cable), high-frequency transmission cable, flat cable, heat-resistant cable, and the like, and is suitably used for transmission cables such as LAN cable (Ethernet Cable) and high-frequency transmission cable.

[0132] As the material of the core wire, a metal conductor material such as copper, aluminum, or the like can be used. The core wire preferably has a diameter of 0.02 mm to 3 mm. The diameter of the core wire is more preferably 0.04 mm or more, further preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. The diameter of the core wire is more preferably 2 mm or less.

[0133] As a specific example of the core wire, for example, AWG (American Wire Gauge) -46 (solid copper wire having a diameter of 40 μm), AWG-26 (solid copper wire having a diameter of 404 μm), AWG-24 (solid copper wire having a diameter of 510 μm), AWG-22 (solid copper wire having a diameter of 635 μm), or the like can be used.

[0134] The thickness of the covering layer is preferably 0.1 mm to 3.0 mm. The thickness of the covering layer is also preferably 2.0 mm or less.

[0135] As the high-frequency transmission cable, a coaxial cable can be given. The coaxial cable generally has a structure in which an inner conductor, an insulating covering layer, an outer conductor layer, and a protective covering layer are sequentially layered from the core to the outer peripheral portion. The molded body containing the fluorine-containing copolymer of the present application can be suitably used as the insulating covering layer containing the fluorine-containing copolymer. The thickness of each layer in the above structure is not particularly limited, and generally, the diameter of the inner conductor is about 0.1 mm to 3 mm, the thickness of the insulating covering layer is about 0.3 mm to 3 mm, the thickness of the outer conductor layer is about 0.5 mm to 10 mm, and the thickness of the protective covering layer is about 0.5 mm to 2 mm.

[0136] The covering layer can contain bubbles, and the bubbles are preferably uniformly distributed in the covering layer.

[0137] The average bubble diameter of the bubbles is not limited, and for example, is preferably 60 μm or less, more preferably 45 μm or less, further preferably 35 μm or less, still further preferably 30 μm or less, particularly preferably 25 μm or less, and especially preferably 23 μm or less. In addition, the average bubble diameter is preferably 0.1 μm or more, and more preferably 1 μm or more. The average bubble diameter can be calculated by obtaining an electron microscope image of a cross section of the electric wire, calculating the diameter of each bubble using image processing, and averaging.

[0138] The foaming ratio of the covering layer can be 20% or more. More preferably, the foaming ratio is 30% or more, further preferably 33% or more, and still further preferably 35% or more. The upper limit is not particularly limited, and for example, is 80%. The upper limit of the foaming ratio can be 60%. The foaming ratio is a value calculated as ((the specific gravity of the electric wire covering material - the specific gravity of the covering layer) / the specific gravity of the electric wire covering material) x 100. The foaming ratio can be adjusted as appropriate according to the use by, for example, adjusting the amount of gas inserted in the extruder described later, or by selecting the type of gas to be dissolved.

[0139] The coated electric wire can also have other layers between the above-mentioned core wire and the above-mentioned coating layer, and can further have other layers (outer layer) around the coating layer. In the case where the coating layer contains bubbles, the electric wire of the present application can also have a two-layer structure (skin-foam) in which a non-foamed layer is interposed between the core wire and the coating layer; a two-layer structure (foam-skin) in which the outer layer is coated with a non-foamed layer; and further a three-layer structure (skin-foam-skin) in which the outer layer of the skin-foam is coated with a non-foamed layer. The non-foamed layer is not particularly limited, and can be a resin layer composed of a TFE / HFP-based copolymer, a TFE / PAVE-based copolymer, a TFE / ethylene-based copolymer, a vinylidene fluoride-based polymer, a polyolefin resin such as polyethylene [PE], a resin such as polyvinyl chloride [PVC], or the like.

[0140] The coated electric wire can be manufactured, for example, by heating the fluorine-containing copolymer using an extruder, extruding the fluorine-containing copolymer onto the core wire in a molten state, and forming the coating layer.

[0141] In forming the coating layer, the above-mentioned coating layer containing bubbles can also be formed by heating the fluorine-containing copolymer, and introducing a gas into the fluorine-containing copolymer in a molten state. As the gas, for example, dichlorofluoromethane, nitrogen, carbon dioxide, or the like, or a mixture of the above-mentioned gases can be used. The gas can be introduced into the heated fluorine-containing copolymer in the form of pressurized gas, or can be generated by mixing a chemical foaming agent in the fluorine-containing copolymer. The gas is dissolved in the molten fluorine-containing copolymer.

[0142] In addition, the fluorine-containing copolymer of the present application can be suitably used as a material for a high-frequency signal transmission product.

[0143] As the above-mentioned high-frequency signal transmission product, there is no particular limitation as long as it is a product for transmission of high-frequency signals, and examples that can be given are (1) an insulating board for a high-frequency circuit, an insulating article for a connecting member, a molded board such as a printed wiring board, (2) a base for a vacuum tube for high frequencies, a molded body such as an antenna cover, (3) a coated electric wire such as a coaxial cable, a LAN cable, and the like. The above-mentioned high-frequency signal transmission product can be suitably used in a device utilizing microwaves, particularly microwaves of 3 GHz to 30 GHz, such as a satellite communication device, a mobile phone base station, and the like.

[0144] In the above-mentioned high-frequency signal transmission product, the fluorine-containing copolymer of the present application can be suitably used as an insulating article from the viewpoint of low tangent of dielectric loss.

[0145] As the above-mentioned (1) molded board, a printed wiring board is preferred from the viewpoint of obtaining good electrical properties. As the above-mentioned printed wiring board, there is no particular limitation, and examples that can be given are, for example, a printed wiring board for an electronic circuit such as a mobile phone, various computers, a communication device, and the like. As the above-mentioned (2) molded body, an antenna cover is preferred from the viewpoint of low dielectric loss.

[0146] The fluorine-containing copolymer of the present application can be molded into a thin film of uniform thickness at a high molding speed by an extrusion molding method, and furthermore, the obtained molded body is excellent in 50°C wear resistance, heat aging resistance, hydrogen low permeability, rigidity at 100°C, 140°C tensile creep resistance, and durability to repeated load, and thus can be suitably used for a film.

[0147] The film of the present application is useful as a release film. The release film can be produced by molding the fluorine-containing copolymer of the present application by melt extrusion molding, calender molding, press molding, flow casting, or the like. From the aspect of obtaining a uniform thin film, the release film can be produced by melt extrusion molding.

[0148] The film of the present application can be applied to the surface of a roller used in an OA device. In addition, the fluorine-containing copolymer of the present application can be molded into a necessary shape by extrusion molding, compression molding, press molding, or the like, and molded into a sheet shape, a film shape, a tube shape, and used as a surface material for an OA device roller or an OA device belt, or the like. In particular, a thin-walled tube or film can be produced by a melt extrusion molding method.

[0149] The fluorine-containing copolymer of the present application can be molded by extrusion molding to obtain a beautiful tube, and furthermore, the obtained molded body is excellent in 50°C wear resistance, heat aging resistance, hydrogen low permeability, rigidity at 100°C, 140°C tensile creep resistance, and durability to repeated load, and thus can be suitably used for a tube. Therefore, the tube containing the fluorine-containing copolymer of the present application can be produced at a high productivity, and has a beautiful shape, and is excellent in 50°C wear resistance, heat aging resistance, hydrogen low permeability, rigidity at 100°C, 140°C tensile creep resistance, and durability to repeated load.

[0150] The above-described embodiments are described, but it is understood that various modifications can be made to the modes and details without departing from the spirit and scope of the claims.

[0151] Examples

[0152] Next, the embodiments of the present application are described with examples, but the present application is not limited to the examples.

[0153] Each value of the examples is measured by the following method.

[0154] The content of each monomer unit of the fluorine-containing copolymer is measured using an NMR analysis device (for example, AVANCE 300 high temperature probe manufactured by Bruker BioSpin Co., Ltd.) or an infrared absorption measuring device (Spectrum One manufactured by Perkin Elmer Co., Ltd.).

[0155] (-CF2H)

[0156] The number of -CF2H groups of the fluorine-containing copolymer was measured using a nuclear magnetic resonance device, AVANCE-300 (manufactured by Bruker BioSpin), with the measurement temperature set to (the melting point of the polymer + 20) °C 19 F-NMR measurement, from the peak integral value of -CF2H groups.

[0157] (-COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2)

[0158] The dry powder or pellets obtained in the examples and comparative examples were cold-pressed to form a film having a thickness of 0.25 mm to 0.3 mm. The film was scanned 40 times by a Fourier transform infrared spectroscopy analysis device [FT-IR (Spectrum One, manufactured by PerkinElmer)], and analyzed to obtain an infrared absorption spectrum. The obtained infrared absorption spectrum was compared with the infrared absorption spectrum of a known film, and the type of terminal group was determined. In addition, from the absorption peak of a specific functional group appearing in the differential spectrum of the obtained infrared absorption spectrum and the infrared absorption spectrum of a known film, the number of functional groups N per 1 x 10 6 carbon atoms in the sample was calculated according to the following formula (A).

[0159] N = I x K / t (A)

[0160] I: absorbance

[0161] K: correction factor

[0162] t: thickness of the film (mm)

[0163] As a reference, with respect to the functional groups in the examples, the absorption frequency, molar absorption coefficient, and correction factor are shown in Table 2. In addition, the molar absorption coefficient was determined from the FT-IR measurement data of a low molecular model compound.

[0164] [Table 2]

[0165] Table 2

[0166]

[0167] (melt flow rate (MFR))

[0168] With respect to the MFR of the fluorine-containing copolymer, the mass (g / 10 minutes) of the polymer flowing out from a die having an inner diameter of 2 mm and a length of 8 mm per 10 minutes was measured at 372°C under a load of 5 kg using a melt flow indexer G-01 (manufactured by Toyo Seiki Jiki K.K.), and the MFR was calculated therefrom.

[0169] (melting point)

[0170] Regarding the melting point of the fluorine-containing copolymer, a differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-Tech Science Corporation) was used to perform a first temperature increase from 200°C to 350°C at a temperature increase rate of 10°C / minute, followed by cooling from 350°C to 200°C at a cooling rate of 10°C / minute, and then a second temperature increase from 200°C to 350°C at a temperature increase rate of 10°C / minute, and the melting point was determined from the peak value of the melting curve generated during the second temperature increase.

[0171] Example 1

[0172] A 174-L volume autoclave equipped with a stirrer was charged with 40.25 kg of deionized water and 0.419 kg of methanol, and the autoclave was sufficiently subjected to vacuum nitrogen replacement. Thereafter, the autoclave was vacuum degassed, and 40.25 kg of HFP and 0.82 kg of PPVE were charged into the autoclave in the vacuum state, and the autoclave was heated to 25.5°C. Next, TFE was charged until the internal pressure of the autoclave reached 0.970 MPa, and then 1.25 kg of a 8 mass% solution of di(ω-hydroperfluorohexanoyl) peroxide (hereinafter referred to as DHP) was charged into the autoclave, and polymerization was started. The internal pressure of the autoclave at the start of polymerization was set to 0.970 MPa, and the set pressure was maintained by continuously adding TFE. Methanol 0.419 kg was added after 1.5 hours from the start of polymerization. DHP 1.25 kg was added after 2 hours and after 4 hours from the start of polymerization, and the internal pressure was lowered by 0.002 MPa each time, and 0.96 kg was added after 6 hours, and the internal pressure was lowered by 0.002 MPa. Thereafter, DHP 0.25 kg was added every 2 hours until the end of the reaction, and the internal pressure was lowered by 0.002 MPa each time.

[0173] Note that 0.13 kg of PPVE was added at the time when the amount of continuously added TFE reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. In addition, 0.419 kg of methanol was added to the autoclave at the time when the amount of added TFE reached 6.0 kg and 18.1 kg, respectively. Furthermore, the polymerization was ended at the time when the amount of added TFE reached 40.25 kg. After the completion of the polymerization, unreacted TFE and HFP were released, and a wet powder was obtained. Thereafter, the wet powder was washed with pure water, and then dried at 150°C for 10 hours, and a dry powder of 43.4 kg was obtained.

[0174] The obtained powder was melt-extruded using a screw extruder (trade name: PCM46, manufactured by Tekno Process Co., Ltd.) at 370°C to obtain pellets of the copolymer. Using the obtained pellets, the HFP content and the PPVE content were measured by the above-described methods. The results are shown in Table 3.

[0175] After the obtained pellets were degassed at 200°C for 72 hours using an electric furnace, the pellets were introduced into a vacuum vibration type reaction apparatus VVD-30 (manufactured by Okawara Mfg. Co., Ltd.) and warmed to 110°C. After vacuumizing, F2 gas diluted to 20 vol% with N2 gas was introduced to atmospheric pressure. After 0.5 hours from the start of the introduction of the F2 gas, the F2 gas was temporarily vacuumized and introduced again. Further, after 0.5 hours from the introduction, the F2 gas was vacuumized again and introduced again. Thereafter, the operation of introducing and vacuumizing the F2 gas was continued once in 1 hour, and the reaction was performed at a temperature of 110°C for 8 hours. After the completion of the reaction, the inside of the reactor was sufficiently replaced with N2 gas, and the fluorination reaction was completed to obtain pellets. Using the obtained pellets, various physical properties were measured by the above-described methods. The results are shown in Table 3.

[0176] Example 2

[0177] The amount of methanol introduced before the start of polymerization was changed to 0.518 kg, the amounts of methanol added in portions after the start of polymerization were changed to 0.518 kg each, the amount of PPVE introduced before the start of polymerization was changed to 1.03 kg, the amounts of PPVE added in portions after the start of polymerization were changed to 0.17 kg each, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.970 MPa, and otherwise, copolymer pellets were obtained in the same manner as in Example 1. Using the obtained pellets, various physical properties were measured by the above-described methods without fluorination. The results are shown in Table 3.

[0178] Example 3

[0179] The amount of methanol introduced before the start of polymerization was changed to 0.516 kg, the amounts of methanol added in portions after the start of polymerization were changed to 0.516 kg each, the amount of PPVE introduced before the start of polymerization was changed to 1.37 kg, the amounts of PPVE added in portions after the start of polymerization were changed to 0.22 kg each, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.970 MPa, and otherwise, copolymer pellets were obtained in the same manner as in Example 1. Using the obtained pellets, the HFP content and the PPVE content were measured by the above-described methods. The results are shown in Table 3.

[0180] The obtained pellets were degassed at 200°C for 8 hours in an electric furnace, and then introduced into a vacuum vibration type reaction apparatus VVD-30 (manufactured by Okawara Mfg. Co., Ltd.) and warmed to 200°C. After vacuumizing, F2 gas diluted to 20 vol% with N2 gas was introduced to the atmosphere pressure. After 0.5 hours from the start of the introduction of the F2 gas, the F2 gas was temporarily vacuumized and introduced again. Further, after 0.5 hours from the introduction, the F2 gas was vacuumized again and introduced again. Thereafter, the operation of the introduction and vacuumization of the F2 gas was repeated once every 1 hour, and the reaction was carried out at 200°C for 8 hours. After the completion of the reaction, the inside of the reactor was sufficiently replaced with N2 gas, and the fluorination reaction was completed, to obtain pellets. Using the obtained pellets, various physical properties were measured by the above-described methods. The results are shown in Table 3.

[0181] Example 4

[0182] The amount of the methanol introduced before the start of the polymerization was changed to 0.526 kg, the amounts of the methanol separately added after the start of the polymerization were changed to 0.526 kg each, the amount of the PPVE introduced before the start of the polymerization was changed to 1.51 kg, the amounts of the PPVE separately added after the start of the polymerization were changed to 0.24 kg each, and the set pressure inside the autoclave before and after the start of the polymerization was changed to 0.970 MPa, and otherwise, the copolymer pellets were obtained in the same manner as in Example 1. Using the obtained pellets, the HFP content and the PPVE content were measured by the above-described methods. The results are shown in Table 3.

[0183] The obtained pellets were fluorinated in the same manner as in Example 3. Using the obtained pellets, various physical properties were measured by the above-described methods. The results are shown in Table 3.

[0184] Example 5

[0185] The amount of the methanol introduced before the start of the polymerization was changed to 0.450 kg, the amounts of the methanol separately added after the start of the polymerization were changed to 0.450 kg each, the amount of the PPVE introduced before the start of the polymerization was changed to 1.09 kg, the amounts of the PPVE separately added after the start of the polymerization were changed to 0.19 kg each, and the set pressure inside the autoclave before and after the start of the polymerization was changed to 0.948 MPa, and otherwise, the copolymer pellets were obtained in the same manner as in Example 1. Using the obtained pellets, the HFP content and the PPVE content were measured by the above-described methods. The results are shown in Table 3.

[0186] The obtained pellets were fluorinated in the same manner as in Example 3. Using the obtained pellets, various physical properties were measured by the above-described methods. The results are shown in Table 3.

[0187] Comparative Example 1

[0188] The amount of methanol charged before the start of polymerization was changed to 0.257 kg, the amounts of methanol separately charged after the start of polymerization were changed to 0.257 kg each, the amount of PPVE charged before the start of polymerization was changed to 1.12 kg, the amounts of PPVE separately charged after the start of polymerization were changed to 0.23 kg each, the set pressure inside the autoclave before and after the start of polymerization was changed to 0.892 MPa, and otherwise the same as in Example 1 to obtain copolymer pellets. The obtained pellets were used without fluorination, and various physical properties were measured by the above-described methods. The results are shown in Table 3.

[0189] Comparative Example 2

[0190] The amount of methanol charged before the start of polymerization was changed to 0.374 kg, the amounts of methanol separately charged after the start of polymerization were changed to 0.374 kg each, the amount of PPVE charged before the start of polymerization was changed to 1.54 kg, the amounts of PPVE separately charged after the start of polymerization were changed to 0.29 kg each, the set pressure inside the autoclave before and after the start of polymerization was changed to 0.924 MPa, and otherwise the same as in Example 1 to obtain copolymer pellets. The obtained pellets were used without fluorination, and various physical properties were measured by the above-described methods. The results are shown in Table 3.

[0191] Comparative Example 3

[0192] The amount of methanol charged before the start of polymerization was changed to 0.502 kg, the amounts of methanol separately charged after the start of polymerization were changed to 0.502 kg each, the amount of PPVE charged before the start of polymerization was changed to 0.47 kg, the amounts of PPVE separately charged after the start of polymerization were changed to 0.09 kg each, the set pressure inside the autoclave before and after the start of polymerization was changed to 0.924 MPa, and otherwise the same as in Example 1 to obtain copolymer pellets. The obtained pellets were used without fluorination, and various physical properties were measured by the above-described methods. The results are shown in Table 3.

[0193] Comparative Example 4

[0194] 0.945 kg of deionized water and 0.014 kg of methanol were added to a 4 L autoclave equipped with a stirrer, and the autoclave was thoroughly purged with nitrogen under vacuum. Then, the autoclave was degassed under vacuum, and 0.945 kg of HFP was added to the vacuum-sealed autoclave. The autoclave was then heated to 25.5 °C. Next, TFE was added until the internal pressure of the autoclave reached 0.970 MPa. Then, 0.029 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to begin polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.970 MPa and maintained by continuously adding TFE. 0.014 kg of methanol was added 1.5 hours after the start of polymerization. 0.029 kg of DHP was added 2 hours and 4 hours after the start of polymerization, and the internal pressure was reduced by 0.002 MPa each time.

[0195] Additionally, when the amount of TFE added reached 0.141 kg, 0.014 kg of methanol was added to the autoclave. The polymerization was terminated when the amount of TFE added reached 0.473 kg. After polymerization, unreacted TFE and HFP were released, yielding a wet powder. This wet powder was then washed with pure water and dried at 150°C for 10 hours to obtain 0.504 kg of dry powder.

[0196] The obtained powder was utilized The copolymer granules were obtained by melt extrusion at 370°C using a screw extruder (manufactured by Imoto Manufacturing Co., Ltd.). The HFP and PPVE contents of the obtained granules were determined using the method described above. The results are shown in Table 3.

[0197] The obtained granules were degassed in an electric furnace at 200°C for 8 hours, then placed in a 500ml portable reactor (TVS1 type, manufactured by a pressure-resistant glass industry company) and heated to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, a temporary vacuum was applied, and F2 gas was introduced again. Then, after another 0.5 hours, a vacuum was applied again, and F2 gas was introduced again. This process of introducing F2 gas and evacuating vacuum was repeated once every hour, and the reaction was carried out at 200°C for 8 hours. After the reaction was completed, the reactor was completely replaced with N2 gas to stop the fluorination reaction, yielding the granules. The obtained granules were used to determine various physical properties using the above method. The results are shown in Table 3.

[0198] Comparative Example 5

[0199] The amount of methanol charged before the start of polymerization was changed to 0.749 kg, the amounts of methanol separately charged after the start of polymerization were changed to 0.749 kg each, the amount of PPVE charged before the start of polymerization was changed to 1.53 kg, the amounts of PPVE separately charged after the start of polymerization were changed to 0.19 kg each, the temperature of the autoclave was changed to 23°C, the set pressure inside the autoclave before and after the start of polymerization was changed to 0.994 MPa, and except for these, copolymer pellets were obtained in the same manner as in Example 1. The HFP content and the PPVE content were measured by the above-described methods using the obtained pellets. The results are shown in Table 3.

[0200] The obtained pellets were fluorinated in the same manner as in Example 3. Various physical properties were measured by the above-described methods using the obtained pellets. The results are shown in Table 3.

[0201] Comparative Example 6

[0202] The amount of methanol charged before the start of polymerization was changed to 0.570 kg, the amounts of methanol separately charged after the start of polymerization were changed to 0.570 kg each, the amount of PPVE charged before the start of polymerization was changed to 1.09 kg, the amounts of PPVE separately charged after the start of polymerization were changed to 0.19 kg each, the set pressure inside the autoclave before and after the start of polymerization was changed to 0.948 MPa, and except for these, copolymer pellets were obtained in the same manner as in Example 1. The HFP content and the PPVE content were measured by the above-described methods using the obtained pellets. The results are shown in Table 3.

[0203] The obtained pellets were fluorinated in the same manner as in Example 3. Various physical properties were measured by the above-described methods using the obtained pellets. The results are shown in Table 3.

[0204] Comparative Example 7

[0205] The amount of methanol charged before the start of polymerization was changed to 0.407 kg, the amounts of methanol separately charged after the start of polymerization were changed to 0.407 kg each, the amount of PPVE charged before the start of polymerization was changed to 2.40 kg, the amounts of PPVE separately charged after the start of polymerization were changed to 0.37 kg each, the set pressure inside the autoclave before and after the start of polymerization was changed to 0.989 MPa, and except for these, copolymer pellets were obtained in the same manner as in Example 1. Various physical properties were measured by the above-described methods using the obtained pellets without fluorination. The results are shown in Table 3.

[0206] Comparative Example 8

[0207] The amount of methanol added before the start of polymerization was changed to 0.592 kg, the amounts of methanol separately added after the start of polymerization were each changed to 0.592 kg, the amount of PPVE added before the start of polymerization was changed to 1.41 kg, the amounts of PPVE separately added after the start of polymerization were each changed to 0.22 kg, the set pressure inside the autoclave before and after the start of polymerization was changed to 0.979 MPa, and apart from this, copolymer pellets were obtained in the same way as in Example 1. The obtained pellets were used without fluorination, and various physical properties were measured by the above-described methods. The results are shown in Table 3.

[0208] Comparative Example 9

[0209] An autoclave with a stirrer having a volume of 4 L was charged with 945 g of deionized water and 3.1 g of methanol, and nitrogen was introduced into the autoclave while the inside of the autoclave was being sufficiently evacuated. After that, the inside of the autoclave was vacuum-deaerated, 945 g of HFP and 32.3 g of PPVE were added to the autoclave in the vacuum state, and the autoclave was heated to 25.5°C. Next, TFE was added until the internal pressure of the autoclave reached 0.970 MPa, and then 29.4 g of a 8 mass% solution of di(ω-hydroperfluorohexanoyl) peroxide (hereinafter referred to as DHP) was added to the inside of the autoclave, and polymerization was started. The internal pressure of the autoclave at the start of polymerization was set to 0.970 MPa, and the set pressure was maintained by continuously adding TFE. Methanol was added 1.5 hours after the start of polymerization, 3.1 g. DHP was added 2 hours and 4 hours after the start of polymerization, and the internal pressure was lowered by 0.002 MPa each time, and 22.6 g was added 6 hours after the start of polymerization, and the internal pressure was lowered by 0.002 MPa. After that, DHP was added 6.0 g every 2 hours until the end of the reaction, and the internal pressure was lowered by 0.002 MPa each time.

[0210] Note that 5.2 g of PPVE was added at the time when the amount of continuously added TFE reached 190 g and 380 g, respectively. In addition, 3.1 g of methanol was added to the inside of the autoclave at the time when the amount of added TFE reached 140 g. Also, the polymerization was ended at the time when the amount of added TFE reached 380 g. After the end of the polymerization, unreacted TFE and HFP were released, and a wet powder was obtained. After that, the wet powder was washed with pure water, and after drying at 150°C for 10 hours and at 205°C for 24 hours, a dried powder of 411 g was obtained. Using the obtained powder, the HFP content and the PEVE content were measured by the above-described methods. The results are shown in Table 3.

[0211] The obtained powder was put in a 500-ml portable reactor Model TVS1 (manufactured by Taikan Glass Industry Co., Ltd.) and heated to 200°C. After vacuumizing, F2 gas diluted to 20 vol% with N2 gas was introduced to the atmospheric pressure. After 0.5 hours from the start of the introduction of the F2 gas, the F2 gas was temporarily vacuumized and introduced again. Further, after 0.5 hours therefrom, the F2 gas was vacuumized again and introduced again. Thereafter, the operation of the introduction and vacuumization of the F2 gas was continued once in 1 hour, and the reaction was carried out at a temperature of 200°C for 8 hours. After the completion of the reaction, the reactor was sufficiently replaced with N2 gas, and the fluorination reaction was completed to obtain a powder. Using the obtained powder, various physical properties were measured by the above-described methods. The results are shown in Table 3.

[0212] [Table 3]

[0213] Table 3

[0214]

[0215] The notation of "<9" in Table 3 means that the number of -CF2H groups is less than 9. The notation of "<6" in Table 3 means that the total number (the number of functional groups N) of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, and -CONH2 is less than 6.

[0216] Next, using the obtained pellets, the following properties were evaluated. The results are shown in Table 4.

[0217] (Wear Test)

[0218] Using the pellets and a hot press molding machine, a sheet-shaped test piece having a thickness of about 0.2 mm was produced, and a test piece of 10 cm x 10 cm was cut therefrom. The produced test piece was fixed on a test stage of a Taber wear tester (No. 101 Taber-type wear tester, manufactured by Anritsu Kikai Kogyo Co., Ltd.), and a wear test was carried out using the Taber wear tester under conditions of a test piece surface temperature of 50°C, a load of 500 g, a wear wheel CS-10 (ground with abrasive paper #240 for 20 turns), and a rotation speed of 60 rpm. The weight of the test piece after 1000 turns was measured, and the weight of the test piece was further measured after a test of 7000 turns using the same test piece. The wear amount was calculated by the following equation.

[0219] Wear amount (mg) = M1 - M2

[0220] M1: weight of test piece after 1000 turns (mg)

[0221] M2: weight of test piece after 7000 turns (mg)

[0222] (Hot Air Cracking Test)

[0223] A sheet-shaped molded body having a thickness of about 2 mm was produced using the pellets and a hot press molding machine. Using a 13.5 mm x 38 mm oblong dumbbell, the obtained sheet was punched, thereby obtaining 3 test pieces. In the center of the long side of each of the obtained test pieces, a notch was cut using a 19 mm x 0.45 mm blade in accordance with ASTM D1693. The 3 notched test pieces were continuously blown with hot air at 200°C for 2 weeks. After the 3 obtained notched test pieces were installed in a stress cracking test jig in accordance with ASTM D1693 and heated at 200°C for 24 hours using an electric furnace, the notch and the periphery thereof were visually observed, and the number of cracks was counted. The heat aging resistance of a piece in which no cracks were generated was excellent.

[0224] O: the number of cracks was 0

[0225] X: the number of cracks was 1 or more

[0226] (hydrogen transmission coefficient)

[0227] A sheet-shaped test piece having a thickness of about 0.1 mm was produced using the pellets and a hot press molding machine. Using the obtained test piece, the hydrogen transmission degree was measured in accordance with the method described in JIS K7126-1:2006 using a differential pressure type gas permeability meter (L100-5000 type gas permeability meter, manufactured by Systech Illinois, Inc.). The hydrogen transmission degree was measured under the conditions of a permeation area of 50.24 cm 2 , a test temperature of 60°C, and a test humidity of 0% RH. Using the obtained hydrogen transmission degree and the thickness of the test piece, the hydrogen transmission coefficient was calculated by the following equation.

[0228] hydrogen transmission coefficient (cm 3 / mm / (m 2 ·24h·atm)) = GTR x d

[0229] GTR: hydrogen transmission degree (cm 3 / (m 2 ·24h·atm)

[0230] d: thickness of test piece (mm)

[0231] (100°C load deflection)

[0232] Using the pellets and a hot press molding machine, a sheet-shaped test piece having a thickness of about 4 mm was produced, and a test piece of 80 x 10 mm was cut therefrom. The test piece was heated at 100°C for 20 hours using an electric furnace. Except for using the obtained test piece, a test was performed under the conditions of a test temperature of 30°C to 150°C, a temperature increase rate of 120°C / hour, a bending stress of 1.8 MPa, and a flatwise method using a thermal deformation tester (manufactured by Seishin Enterprise Co., Ltd.) as described in JIS K-K7191-1. The load deflection ratio was calculated by the following formula. The sheet having a small load deflection ratio at 100°C had excellent rigidity at 100°C.

[0233] Load deflection ratio (%) = a2 / a1 x 100

[0234] a1: thickness of test piece before test (mm)

[0235] a2: deflection amount at 100°C (mm)

[0236] (Tensile creep test)

[0237] The tensile creep strain was measured using a TMA-7100 manufactured by Hitachi High-Technologies Corporation. Using the pellets and a hot press molding machine, a sheet having a thickness of about 0.1 mm was produced, and a sample having a width of 2 mm and a length of 22 mm was produced from the sheet. The sample was installed in a measurement jig at a jig distance of 10 mm. For the sample, a load was applied in a manner such that the cross-sectional load was 3.32 N / mm 2 The displacement (mm) of the length of the sample from the time of 90 minutes after the start of the test to the time of 450 minutes after the start of the test was measured while the sample was placed at 140°C, and the proportion of the displacement (mm) of the length with respect to the initial sample length (10 mm) (tensile creep strain (%)) was calculated. The sheet having a small tensile creep strain (%) measured at 140°C for 450 minutes was less likely to elongate even when a tensile load was applied for a long time in a high-temperature environment, and had excellent high-temperature tensile creep resistance (140°C).

[0238] (Tensile strength after 8,000 cycles)

[0239] The tensile strength after 8,000 cycles was measured using a fatigue testing machine MMT-250NV-10 manufactured by Shimadzu Corporation. Using the pellets and a hot press molding machine, a sheet having a thickness of about 2.4 mm was produced, and a sample having a dumbbell shape (thickness of 2.4 mm, width of 5.0 mm, and measurement portion length of 22 mm) was produced using an ASTM D1708 micro dumbbell. The sample was installed in a measurement jig, and the measurement jig was set in a constant temperature bath at 110°C in a state in which the sample was installed. Tensile stretching in a uniaxial direction was repeatedly performed at a stroke of 0.2 mm and a frequency of 100 Hz, and the tensile strength of each time of stretching (tensile strength at a stroke of +0.2 mm, unit: N) was measured.

[0240] The sheet with high tensile strength after 8,000 cycles maintains high tensile strength even after being subjected to 8,000 loads, and has excellent durability under repeated loads (110°C).

[0241] (Deformation test due to self-weight during melting)

[0242] Using granulation and a hot press molding machine, molded bodies with a diameter of 13 mm and a height of approximately 6.5 mm were produced. These molded bodies were then cut to create test pieces with a height of 6.3 mm. The test pieces were placed in SUS culture dishes and heated in an electric furnace at 330°C for 30 minutes, followed by water cooling. The diameter of the bottom surface of the removed test piece was measured using vernier calipers, and the increase in bottom area was calculated using the following formula.

[0243] Bottom area increase rate (%) = {bottom area of ​​the test piece after heating (mm²)} 2 - Bottom area of ​​the test piece before heating (mm²) 2 )} / Bottom area of ​​the test piece before heating (mm²) 2 )×100

[0244] A lower base area increase rate means that the molded body is less likely to deform under its own weight when molten. Fluorinated copolymers that provide molded bodies with a low base area increase rate are superior in that even when the fluorinated copolymer is molded into thick sheets or large tubes by extrusion molding, the molten molded body is not easily deformed and obtains the desired shape after cooling and solidification.

[0245] (Conditions for wire coating)

[0246] use A wire coating molding machine (manufactured by Tanabe Plastics Machinery Co., Ltd.) extrudes a fluorinated copolymer onto a copper conductor with a conductor diameter of 1.00 mm to obtain a coated wire at the following coating thickness. The wire coating extrusion molding conditions are as follows.

[0247] a) Core conductor: Conductor diameter 1.00mm

[0248] b) Coating thickness: 0.70mm

[0249] c) Diameter of the covered wire: 2.40mm

[0250] d) Wire pulling speed: 3m / minute

[0251] e) Extrusion conditions:

[0252] • Single-screw extrusion molding machine with a barrel shaft diameter of 30mm and an L / D ratio of 22

[0253] • Die head (inner diameter) / piece (outer diameter) = 24.0mm / 10.0mm

[0254] The temperature setting of the extruder: barrel section C-1 (340°C), barrel section C-2 (375°C), barrel section C-3 (390°C), head H (400°C), die section D-1 (400°C), die section D-2 (400°C). The core wire preheating was set to 80°C.

[0255] (Variation in outer diameter)

[0256] The outer diameter of the obtained coated electric wire was measured using an outer diameter measuring device (ODAC18XY manufactured by Zumbach) for 1 hour continuously. The third digit after the decimal point of the outer diameter value deviating the most from the prescribed outer diameter value (2.40 mm) was rounded off, and thus the variation in outer diameter was calculated. The proportion of the absolute value of the difference between the prescribed outer diameter and the variation in outer diameter with respect to the prescribed outer diameter (2.40 mm) (variation rate in outer diameter) was calculated, and evaluated according to the following criteria.

[0257] (Variation rate in outer diameter (%)) = |(variation in outer diameter) - (prescribed outer diameter)| / (prescribed outer diameter) x 100

[0258] ±1%: variation rate in outer diameter is 1% or less

[0259] ±2%: variation rate in outer diameter exceeds 1% and is 2% or less

[0260] x: variation rate in outer diameter exceeds 2%

[0261] (Tubing formability)

[0262] The extruder (TANABE PLASTICS MACHINERY) was used to extrude the pellets to obtain a tube having an outer diameter of 10.0 mm and a wall thickness of 1.0 mm.

[0263] The extrusion molding conditions were as follows.

[0264] a) die inner diameter: 25 mm

[0265] b) mandrel outer diameter: 13 mm

[0266] c) sizing die inner diameter: 10.5 mm

[0267] d) take-up speed: 0.4 m / minute

[0268] e) outer diameter: 10.0 mm

[0269] f) wall thickness: 1.0 mm

[0270] g) extrusion conditions:

[0271] • single screw extrusion molding machine having a barrel shaft diameter = 30 mm and L / D = 22​

[0272] Setting temperature of extruder: barrel section C-1 (350°C), barrel section C-2 (370°C), barrel section C-3 (380°C), head section H-1 (390°C), die section D-1 (390°C), die section D-2 (390°C)

[0273] The obtained tube was observed, and evaluated according to the following criteria. The appearance of the tube was confirmed by visual observation.

[0274] O: good appearance

[0275] X: cross section not circular, flatness or uneven thickness observed, poor appearance

[0276] (Film formability)

[0277] Using An extruder (manufactured by Miki Pulverizing Co., Ltd.) and a T-die were used to form a film from the pellets. The extrusion molding conditions were as follows.

[0278] a) winding speed: 1 m / min

[0279] b) roll temperature: 120°C

[0280] c) film width: 70 mm

[0281] d) thickness: 0.10 mm

[0282] e) extrusion conditions:

[0283] • single screw extrusion molding machine with a cylinder shaft diameter of 14 mm and L / D of 20

[0284] Setting temperature of extruder: barrel section C-1 (330°C), barrel section C-2 (350°C), barrel section C-3 (365°C), T-die section (370°C)

[0285] The extrusion molding of the fluorine-containing copolymer was continued until the fluorine-containing copolymer was stably extruded from the molding machine. Next, a film (width 70 mm) having a length of 11 m or more was produced by extrusion molding the fluorine-containing copolymer in such a manner that the thickness became 0.10 mm. From the end portion of the obtained film, a portion of 10 to 11 m was cut out, and a test piece for measuring variation in thickness (length 1 m, width 70 mm) was produced. The thickness of a total of three points of the center point in the width direction of the end portion of the produced film and two points 25 mm apart from the center point in the width direction was measured. Further, the thickness of a total of nine points of three center points arranged at intervals of 25 cm from the center point in the width direction of the end portion of the film toward the other end portion and two points 25 mm apart from each center point in the width direction was measured. Of the total of 12 measured values, the case where the number of measured values outside the range of ±10% of 0.10 mm was one or less was O, and the case where the number of measured values outside the range of ±10% of 0.10 mm was two or more was X.

[0286] (Immersion test in hydrogen peroxide water)

[0287] Using the pellets and a hot press molding machine, a sheet having a thickness of about 0.2 mm was produced, and a test piece of 15 mm square was produced. Into a 50 mL polypropylene bottle, 10 test pieces and 15 g of a 3 mass% hydrogen peroxide aqueous solution were put, and after heating at 95°C for 20 hours with an electric furnace, it was cooled to room temperature. The test pieces were taken out from the hydrogen peroxide aqueous solution, and a TISAB solution (10) (manufactured by Kanto Chemical Co., Inc.) was added to the residual hydrogen peroxide aqueous solution, and the concentration of fluoride ions in the obtained hydrogen peroxide aqueous solution was measured with a fluoride ion meter. From the obtained measured value, the concentration of fluoride ions per unit weight of the test piece (eluted fluoride ion concentration) was calculated according to the following formula.

[0288] Eluted fluoride ion concentration (mass ppm) = measured value (ppm) x hydrogen peroxide aqueous solution amount (g) / test piece weight (g)

[0289]

Claims

1. A fluorine-containing copolymer containing tetrafluoroethylene units, hexafluoropropylene units and perfluoro(propyl vinyl ether) units, wherein, the content of the tetrafluoroethylene units is 95.00 mole% to 96.06 mole% relative to the total monomer units, the content of the hexafluoropropylene units is 3.55 mole% to 4.10 mole% relative to the total monomer units, the content of the perfluoro(propyl vinyl ether) units is 0.39 mole% to 0.90 mole% relative to the total monomer units, the melt flow rate under a load of 5 kg and at 372°C is 1.0 g / 10 minutes to 9.0 g / 10 minutes. the content of the hexafluoropropylene units is 3.55 mole% to 3.92 mole% relative to the total monomer units. the content of the perfluoro(propyl vinyl ether) units is 0.46 mole% to 0.85 mole% relative to the total monomer units. the melt flow rate under a load of 5 kg and at 372°C is 2.0 g / 10 minutes to 8.0 g / 10 minutes.

6. An injection-molded article containing the fluorine-containing copolymer according to any one of claims 1 to 5.

2. The fluorocopolymer of claim 1, wherein, 7. An extrusion-molded article containing the fluorine-containing copolymer according to any one of claims 1 to 5.

3. The fluorocopolymer of claim 1 or 2, wherein, 8. A transfer-molded article containing the fluorine-containing copolymer according to any one of claims 1 to 5.

4. The fluorocopolymer of claim 1 or 2, wherein, 9. A coated electric wire having a coating layer containing the fluorine-containing copolymer according to any one of claims 1 to 5.

5. The fluorocopolymer of claim 1 or 2, wherein, per 10 6 functional groups of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, and -CH2OH is 90 or less. The molded article is a pipe, a film or a coated electric wire. The molded article is a pipe, a film or a coated electric wire. ​ ​ 10. A molded article comprising the fluorine-containing copolymer according to any one of claims 1 to 5, wherein ​

Citation Information

Patent Citations

  • Fluorinated terpolymers

    JP1977109588A

  • Oriented fluoropolymer film

    CN105916920A

  • Resin composition and molded article

    CN110799593A